Complementary Analysis of Self-Report Instruments in Enhancing the Accuracy of Electroencephalography (EEG) Results in Marketing - Sharifi, Ali; Vakil Alroaia, Younos; Vahedi, Hasan; Hosseini, Seyed Hossein; Raisi Rad , Elahe (AI and Tech in Behavioral and Social Sciences, 2026)
Neuromarketing employs tools such as electroencephalography (EEG) to uncover the unconscious layers of consumer decision-making. However, exclusive reliance on neural data may lead to incomplete and, in some cases, misleading interpretations. Using a systematic review approach, this study identified and analyzed 52 domestic and international studies in which EEG and complementary instruments were applied in the field of marketing. The studies were classified into four categories based on the types of instruments used: exclusive use of EEG/QEEG, self-report instruments, non-self-report complementary instruments, and integrated approaches. The findings indicate that although EEG possesses a strong capability for capturing unconscious responses, its integration with questionnaires, interviews, eye-tracking, physiological indicators, and machine-learning algorithms significantly enhances data interpretation accuracy and the predictive power of consumer behavior models. Furthermore, a considerable gap was observed between domestic and international studies regarding the adoption of multimodal approaches. Accordingly, the present study emphasizes the necessity of developing integrated models and designing standardized protocols to improve the accuracy and validity of neuromarketing findings.